Actin depolymerization is associated with meiotic acceleration in cycloheximide-treated ovine oocytes - German, Sergio D.; Lee, Joon-Hee; Campbell, Keith H.; Sweetman, Dylan; Alberio, Ramiro (Society for the Study of Reproduction, 2015)
Oocytes treated with the protein synthesis inhibitor cycloheximide (CHX) arrest at the germinal vesicle (GV) stage and undergo accelerated GV breakdown (GVBD) after CHX is removed. However, little is known about the underlying mechanism of accelerated meiotic maturation. Here, we investigated this mechanism and found that oocytes released from CHX arrest have higher amounts of cyclin B1 (CCNB1) and phosphorylated mitogen-activated protein kinase (pMAPK) proteins. Increased levels of these factors were not associated with mRNA polyadenylation or increased transcription rates of CCNB1 and MOS (Moloney murine sarcoma viral oncogene homolog) during CHX arrest. We found that treatment of CHX-arrested oocytes with the actin filament-stabilizing agent Jasplakinolide (Jasp) delayed GVBD following release from CHX arrest and that this was correlated with reduced maturation-promoting factor (MPF) activity. These results suggest that CCNB1 mRNAs released from actin filaments during CHX arrest increase CCNB1 transcripts available for translation after release from CHX arrest, leading to the precocious activation of MPF and accelerated meiotic progression.